2020
DOI: 10.1016/j.clineuro.2020.106192
|View full text |Cite
|
Sign up to set email alerts
|

The association of age, body mass index, and frailty with vestibular schwannoma surgical morbidity

Abstract: Objective: To evaluate whether increased body mass index (BMI), age, or frailty influence vestibular schwannoma (VS) short-term surgical morbidity. Methods:The 2005-2017 National Surgical Quality Improvement Program database was queried for patients with VS undergoing surgical resection. Age was stratified according to age <50, 50-64, and ≥65, while BMI was stratified based on a threshold of 30. Frailty score (0-5) was indicated based on functional status, diabetes, chronic obstructive pulmonary disease, conge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(25 citation statements)
references
References 45 publications
0
25
0
Order By: Relevance
“…A single-center retrospective study conducted by Casazza et al found increasing frailty (by mFI score), and not age, independently associated with increasing hospital length of stay—a finding further bolstered by the present analysis. A recent study using the American College of Surgeons National Surgical Quality Improvement Program database arrived at the same finding using a mFI with 5 baseline factors but did not use multivariable analysis to evaluate the comparative influences of age and frailty on complications or clinical outcome. Taken collectively, the body of literature examining outcomes following VS resection demonstrates a significant prognostic value of frailty relative to increasing age alone with respect to clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…A single-center retrospective study conducted by Casazza et al found increasing frailty (by mFI score), and not age, independently associated with increasing hospital length of stay—a finding further bolstered by the present analysis. A recent study using the American College of Surgeons National Surgical Quality Improvement Program database arrived at the same finding using a mFI with 5 baseline factors but did not use multivariable analysis to evaluate the comparative influences of age and frailty on complications or clinical outcome. Taken collectively, the body of literature examining outcomes following VS resection demonstrates a significant prognostic value of frailty relative to increasing age alone with respect to clinical outcome.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, Researchers have discovered that older adults who report dizziness tend to be physically frail, have more chronic diseases and sensory impairments (de Moraes et al, 2011 , 2013 ; Gomez et al, 2011 ; Kammerlind et al, 2016 ). Dizziness, unsteadiness, or lightheadedness is associated with frailty, and in fully adjusted models, frailty was still related to dizziness, unsteadiness, or lightheadedness (O'Connell et al, 2015 ; Goshtasbi et al, 2020 ). Because of the limitations of observational epidemiological studies in eliminating bias (for example, reverse causation and confounding factors), while observational studies have reported a relationship between frailty and vestibular disease, little is known about their causal relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Six studies included in this review evaluated the impact of obesity on postoperative LOS [19,20,22,24,26,28]. Only one study demonstrated that obesity was associated with a longer LOS using the ACS-NSQIP database [26].…”
Section: Length Of Hospital Staymentioning
confidence: 99%